Growth of cucumber seedlings in different varieties as affected by light environment - Ji, Fang; Wei, Siqi; Liu, Nan; Xu, Lijun; Yang, Po (International Journal of Agricultural and Biological Engineering, 2020)
High-quality cucumber seedlings are a prerequisite for ensuring high yield of cucumbers. With the continuous increase of cucumber planting area in China, the demand for high-quality cucumber seedlings is also increasing. One of the important ways to improve the quality of cucumber seedlings is to improve the light environment by using artificial light source. In this study, three cucumber seedlings (cv. Jintong, cv. Yunv and cv. Xiazhiguang) were grown for 23 d under eight levels of daily light integral (DLI) at 4.3 mol/(m2·d), 8.6 mol/(m2·d), 10.1 mol/(m2·d), 13.0 mol/(m2·d), 5.8 mol/(m2·d), 11.5 mol/(m2·d), 14.4 mol/(m2·d) and 17.3 mol/(m2·d), respectively. The results showed that when DLI was 14.4 mol/(m2·d), the seedling height, stem diameter, total leaf area and shoot dry/fresh weight of all three cucumber cultivars reached the maximum, while hypocotyl length decreased with the increase of light intensity. When DLI was 14.4 mol/(m2·d), Jintong and Xiazhiguang had the highest health index, which were 49.29 and 28.56, respectively, while that of Yunv was 81.59 (DLI = 14.4 mol/(m2·d)). With the increase of DLI, the photosynthetic capacity of cucumber increases gradually. The highest net photosynthetic rate was shown at DLI of 14.4 mol/(m2·d), while the chlorophyll content of cucumber seedlings of all three cultivars were less affected by DLI. Jintong and Yunv had the highest chlorophyll content when DLI was 8.6 mol/(m2·d) because they were adapted to low-light environment. In conclusion, the DLI of 14.4 mol/(m2·d) for Jintong and Xiazhiguang, while that of 17.3 mol/(m2·d) for Yunv are suggested for the light environment design of factory-cultivated seedling for cucumber.Keywords: cucumber seedling, daily light integral (DLI), growth, photosynthesisDOI: 10.25165/j.ijabe.20201305.5566Citation: Ji F, Wei S Q, Liu N, Xu L J, Yang P. Growth of cucumber seedlings in different varieties as affected by light environment. Int J Agric & Biol Eng, 2020; 13(5): 73–78.